1985
DOI: 10.1007/bf00329810
|View full text |Cite
|
Sign up to set email alerts
|

Kinetochore microtubules and chromosome movement during prometaphase in Drosophila melanogaster spermatocytes studied in life and with the electron microscope

Abstract: Prometaphase I chromosome behavior was examined in wild-type Drosophila melanogaster primary spermatocytes. Cine analysis of live cells reveals that bivalents exhibit complex motions that include (1) transient bipolar orientations, (2) simultaneous reorientation of homologous kinetochores, (3) movements not parallel to the spindle axis, and (4) movement along the nuclear membrane. --Kinetochores and kinetochore microtubule have been analyzed for bivalents previously studied in life. The results suggest that mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 16 publications
4
29
1
Order By: Relevance
“…In support of our model, recent data indicate that the reorientation of univalents [Steffen, 1986;Ault, unpublished observation] and bivalents [Church and Lin, 1985;Nicklas and Kubai, 1985;Ault and Nicklas, 19891 during meiosis I depends on the reorienting kinetochore capturing MTs from the other pole. Yet, although it has been proposed that the simultaneous attachment of a single kinetochore to both poles is common during mitosis [Heneen, 19751, there is little evidence to support this supposition.…”
Section: The Mechanism Of Kinetochore Reorientation During Mitosissupporting
confidence: 81%
“…In support of our model, recent data indicate that the reorientation of univalents [Steffen, 1986;Ault, unpublished observation] and bivalents [Church and Lin, 1985;Nicklas and Kubai, 1985;Ault and Nicklas, 19891 during meiosis I depends on the reorienting kinetochore capturing MTs from the other pole. Yet, although it has been proposed that the simultaneous attachment of a single kinetochore to both poles is common during mitosis [Heneen, 19751, there is little evidence to support this supposition.…”
Section: The Mechanism Of Kinetochore Reorientation During Mitosissupporting
confidence: 81%
“…This is in contrast to protocols enabling short-term (ca. 3 hr) observations in Voltalef oil 41,42 . The procedures described above for cultivation and pharmacological treatment of pupal testes and single male germ-line cysts are easily adaptable to the many genetic, epigenetic, cell biological, or developmental questions that can be researched in Drosophila spermatogenesis.…”
Section: Discussionmentioning
confidence: 97%
“…In D. pratensis, however, it is evident that, despite the multivalent and male involved, abnormal second spermatocytes are almost invariably less than expected from non-alternate MI orientation, which also occurs in trivalents of this species . This suggests that reorientation towards alternate configurations occurs effectively even at late MI, which is not surprising since Church & Lin (1985) showed that in Drosophila spermatocytes, bivalents can reorient up to 10 mm before AT (see also Nicklas, 1985 andNicklas &Kubai, 1985). An alternative possibility (although not supported by factual evidence) is that aneuploid cells are eliminated during intekinesis.…”
Section: Discussionmentioning
confidence: 98%